Analisis penggunaan e-learning berbasis Multimedia Cognitive Theory Approach pada pembelajaran Geografi di masa pandemi COVID-19 - Robby Hilmi Rachmadian; Rachel Michellia; Leni Fitrianingsih; Dhella Widy A; Alfyananda Kurnia Putra (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial (JIHI3S), 2021)
The use of multimedia in the learning process, especially geography learning, has the aim of increasing students' understanding of the material provided, increasing learning motivation in students and creating meaningful learning. The activeness of students is an indicator in the implementation of meaningful learning. The cognitive activity of students is very necessary during learning, but the cognitive level of each student has a different capacity. In this case, educators must create a learning innovation that is easily accepted by students, one of which is the use of multimedia in geography learning. The use of multimedia in the learning process has sensitivity to the cognitive load of each learner. The use of e-learning in the geography learning process during the COVID-19 pandemic presents its own challenges for teachers to provide effective learning so that students can use their cognitive processes to the fullest. Thus, further analysis is needed regarding the use of e-learning with a multimedia cognitive theory approach in current geography learning. The research methodology used in this research is qualitative research. The type of data obtained is qualitative data. The data analysis technique used a qualitative descriptive analysis. The result of this study is to provide a new understanding and analysis of the use of e-learning by using a multimedia cognitive theory approach in geography learning during the COVID-19 pandemic. Penggunaan multimedia dalam proses pembelajaran khususnya pembelajaran geografi memiliki tujuan meningkatkan pemahaman peserta didik terhadap materi yang diberikan, meningkatkan motivasi belajar pada peserta didik dan menciptakan pembelajaran yang bermakna. Keaktifan peserta didik menjadi indikator dalam pelaksanaan pembelajaran bermakna. Aktivitas kognitif peserta didik sangat diperlukan selama pembelajaran berlangsung, namun tingkat kognitif setiap peserta didik memiliki kapasitas yang berbeda. Dalam hal ini, tenaga pendidik harus menciptakan sebuah inovasi pembelajaran yang mudah diterima oleh peserta didik, salah satunya pemanfaatan multimedia dalam pembelajaran geografi. Penggunaan multimedia dalam proses pembelajaran memiliki sensitivitas pada beban kognitif setiap peserta didik. Penggunaan e-learning pada proses pembelajaran geografi di masa pandemi COVID-19 memberikan tantangan tersendiri bagi pengajar untuk memberikan pembelajaran yang efektif agar siswa dapat menggunakan proses kognitifnya dengan maksimal. Dengan demikian, diperlukan analisis lebih lanjut mengenai penggunaan e-learning dengan pendekatan teori kognitif multimedia pada pembelajaran geografi saat ini. Metodologi penelitian yang digunakan dalam penelitian ini adalah penelitian kualitatif. Jenis data yang diperoleh adalah data kualitatif. Teknik analisis data menggunakan analisis deskriptif kualitatif. Hasil dari penelitian ini adalah memberikan pemahaman baru serta analisis tentang penggunaan e-learning dengan menggunakan pendekatan teori kognitif multimedia pada pembelajaran geografi di masa pandemi COVID-19.